PEMETAAN KESESUAIAN HABITAT OWA JAWA (Hylobates moloch Audebert 1797) DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK (Habitat Suitability Mapping of Sylvery Gibbon (Hylobates moloch Audebert 1797) in Gunung Halimun-Salak National Park) - Helianthi Dewi; Lilik Budi Prasetyo; Dones Rinaldi (Media Konservasi, 2007)
Sylvery gibbon (Hylobates moloch) is endemic species in western part of Java Island. Gunung Halimun-Salak National Park currently is known to be place of viable population for the species. Threatened on habitat is a primary problem for its conservation. Therefore it is an urgent need to study its habitat suitability distribution. The main objectives of the research are: 1) to analyze habitat suitability of sylvery gibbon (H. moloch Audebert) in Gunung Halimun-Salak National Park using Geographical Information System, 2) to examine of its habitat condition. Result shows that habitat suitability of the species can be accurately predicted by using thematic maps of elevation, slope, distance from road, river, and land cover. Based on our prediction, potential habitat for sylvery gibbon in Gunung Halimun-Salak National Park is about 33018 ha, in which classified as lowest habitat suitability (846.27 Ha), intermediate habitat suitability (12,311.9 Ha) and high habitat suitability (24,624.2 Ha). Most of the suitable habitat is under forest cover.Keywords: Habitat, Hylobates moloch, suitability